Motivational factors of voluntourists : a case studi of Juara Turtle project, Tioman Islamd [electronic resource] - Mohd. Raizal Abd. Rahim, 1980- (2011)
Thesis (Sarjana Sains (Perancangan Pelancongan)) - Universiti Teknologi Malaysia, 2011